Agmatine-attenuated cognitive and social deficits in subchronic MK-801 model of schizophrenia in rats - ARICIOĞLU, FEYZA (TAYLOR & FRANCIS LTD, 2018)
INTRODUCTION: Schizophrenia is one of the most severe psychiatric disorders with about 1% prevalence. It has been proved that glutamatergic N-methyl-d-aspartate (NMDA) receptor antagonists such as MK-801 and phencyclidine cause schizophrenia-like behaviours in rodents. Agmatine is an endogenous amine synthesized from decarboxylation of arginine and has been thought to be a neurotransmitter/neuromodulator. It binds to imidazoline and alfa adrenergic receptors and blocks cation channelled receptors, such as nicotinic acetylcholine, 5-HT3 serotonergic, and NMDA receptors. It is an endogenous inhibitor of nitric oxide synthase. A limited number of studies showed that agmatine attenuates sensorimotor gating deficit, which is an important parameter for schizophrenia, and improves cognitive deficits in rats. Despite this, it has also been shown that high doses of agmatine impaired sensorimotor gating. Herein, the aim of our study is to investigate the effect of subchronic agmatine treatment on sensorimotor gating, visual recognition memory, and social functions in subchronic MK-801 model of schizophrenia in rats. METHODS: Wistar Hannover rats were divided into four groups as control (dimethyl sulphoxide), MK-801 (0.2mg/kg), MK-801+agmatine (20mg/kg), and MK-801+risperidone (0.5mg/kg)(n=8 per group). MK-801 was subcutaneously injected once a day for 14 days. Agmatine and risperidone were administered intraperitoneally in the last seven days of MK-801 injections. On day 14, agmatine or risperidone was injected 15 minutes before MK-801 and MK-801 15 minutes before prepulse inhibition of the acoustic startle response (PPI) test. After the seven days washout period, social interaction (SI) test and novel object recognition test (NORT) were performed. One-way analysis of variance (ANOVA) or two-way ANOVA was used for statistical evaluation of NORT, SI, and PPI, respectively. Paired Student's t-test was used for the comparison of rat's affinity to a familiar and novel object in NORT. RESULTS: MK-801 administration significantly decreased prepulse inhibition of rats in the PPI test (p<.001). In addition to this, MK-801 decreased startle response to pulse-alone trials and increased basal activity measured by the magnitude of no stimulus trials compared to the control group (p<.05). Agmatine treatment did not improve MK-801-induced PPI, startle response, or basal activity deficits while risperidone blocked the disruptive effect of MK-801 (p<.05). In NORT, the MK-801 group had significantly lower discrimination index (p<.05), whereas both the agmatine and risperidone treatments substantially increased this index (p<.01). Moreover, MK-801 injections not only decreased sniffing (p<.01) and following (p<.01) behaviours but also increased avoiding behaviour (p<.001) in SI. Agmatine partially treated social deficits (p<.001) while risperidone was reversed all of them (p<.01). CONCLUSIONS: Subchronic MK-801 administration revealed sensorimotor gating, social and cognitive deficits in rats. Subchronic agmatine treatment improved cognitive deficits and increased socialization in rats although it was ineffective for sensorimotor gating deficits. Our results indicate that agmatine might be a modulator for negative and cognitive symptoms of schizophrenia, which are still unsolved issues for schizophrenia patients.
Keywords: Agmatine; MK-801; risperidone; prepulse inhibition; schizophrenia; NEGATIVE SYMPTOMS; PREPULSE INHIBITION; OBJECT RECOGNITION; IMIDAZOLINE RECEPTORS; ENDOGENOUS LIGAND; MICE; PHENCYCLIDINE; GLUTAMATE; MEMORY; NEUROTRANSMITTER